Analysis of microstructures and macrotextures for different apple cultivars based on parenchyma morphology. Issue 4 (13th February 2016) - Hou, Jumin; Sun, Yonghai; Chen, Fangyuan; Yu, Libo; Mao, Qian; Wang, Lu; Guo, Xiaolei; Liu, Chao
ABSTRACT: Fuji, Golden Delicious, and Jonagold parenchyma were imaged by confocal laser scanning microscopy to be extracted morphology characteristics, which were used to analyze the relationship with macrotexture of apples tested by penetration and compression. Before analyzing the relationship, the significantly different morphology parameters were reduced in dimensions by principal component analysis and were proved to be availably used for distinguishing the different apple cultivars. For compression results, cell did not absolutely determine the hardness in different apple cultivars, and the pore should also be taken into consideration. With the same size in cell feret diameter, the bigger the pore feret diameter was, the softer the apple became. If no difference existed in pore feret diameter size, the cultivar became harder with a narrower distribution in cell feret diameter. The texture parameters were compared with the roundness parameters in the same or inverse changing trends to explore the relationship. High correlations were found between the texture parameters (energy required in whole penetration (Wt), fracture force (Fp), crispness) and pore solidity ( R 2  > 0.924, P < 0.001). Compactness of parenchyma played an important role in fruit texture. This research could provide the comprehension about relationship between microstructure and macrotexture of apple cultivars and morphological values for modeling apple parenchyma, contributing to numerical simulation for constitutive relation of fruit. Microsc. Res. Tech. 79:304–312, 2016 . © 2016 Wiley Periodicals, Inc.